An investigation of statistical power for continuous arterial spin labeling imaging at 1.5 T - Asllani, Iris; Borogovac, Ajna; Wright, Clinton; Sacco, Ralph; Brown, Truman R.; Zarahn, Eric (NeuroImage (Orlando, Fla.), 2008)
Variance estimates can be used in conjunction with scientifically meaningful effect sizes to design experiments with type II error control. Here we present estimates of intra- and inter-subject variances for region of interest (ROI) from resting cerebral blood flow (CBF) maps obtained using whole brain, spin echo echoplanar (SE-EPI) continuous arterial spin labeling (CASL) imaging on 52 elderly subjects (age=70.5±7.9 years, 29 males). There was substantial intrasubject systematic variability in CBF of gray matter ROIs corresponding to a range of standard deviations=[39–168] (ml/(100 g min)). This variability was mainly due to two factors: (1) an expected inverse relationship between ROI volume and intrasubject variance and (2) an increased effective post-labeling delay for more superior slices acquired later in the sequence. For example, intrasubject variance in Brodmann area 4 (BA 4) was ∼8 times larger than in hippocampus, despite their similar gray matter volumes. Estimated ROI-wise power was computed for various numbers of acquired CBF images, numbers of subjects, and CBF effect sizes for two experimental designs: independent sample t-test and paired t-test. The theoretical effects of pulse sequence and field strength on general applicability of these results are discussed.